The effect of empowerment on English language teachers' commitment to schools: the mediation of teachers' attitudes towards curriculum reform - Boudouaia, Azzeddine; Miqdad, Khalil; AL-Qadri, Abdo Hasan; Saraa, Nadia; Belmamoune, Souheila; Bariu Ntorukiri, Timothy; Xingfang, Yang; Oda Abunamous, Mohammed; Mouissi, Mokhtar (Innovation in language learning and teaching, 2024)
The current study aimed to examine the effect of empowerment on English language teachers' commitment to schools and attitudes towards curriculum reform and the mediation effect of teachers' attitudes towards curriculum reform on the relationship between the teacher's empowerment and commitment to schools. A questionnaire was used to collect data from a sample of 332 middle school English teachers in Algeria. The questionnaire included teachers' empowerment questionnaire model of Yin et al. ( 2013 . "The Effect of Trust on Teacher Empowerment: The Mediation of Teacher Efficacy." Educational Studies 39 (1): 13-28), the Organisational Commitment scale of Meyer & Allen ( 1997 ) and the Attitude toward Change Instrument of Dunham et al. ( 1989 ). The results advocated a significant and positive correlation between the teachers' empowerment, attitudes towards curriculum reform, and commitment to schools. The findings also revealed that teachers' attitudes towards curriculum reform had a signiﬁcant mediation effect on the relationship between empowerment and school commitment. The extent to which teachers believe they are empowered and have a role and contribution in shaping the curriculum of their school has a direct bearing on their dedication to their jobs. The study suggested that the ministry of national education should consider the role of TATCR, TE, and TCTS together as important.